Collection System Topology for Deep-Sea Offshore Wind Farms Considering Wind Characteristics - Fu, Yang; Liu, Yang; Huang, Ling-ling; Ying, Feixiang; Li, Fangxing (IEEE transactions on energy conversion, 2022)
DC series-parallel collection system has recently been widely discussed for integrating deep-sea OWFs because it saves the offshore HVDC stations. However, comparing with traditional offshore electrical collection systems, there is a unique operational problem introducing by the DC series-parallel system that is the wind power curtailment caused by the wind power fluctuations. In this paper, a rigorous mathematical analysis of wind power curtailment is conducted, and an optimization model considering wind power curtailment for DC series-parallel collection systems is proposed. To address the particularities of the series-parallel collection system in graph theory, an improved parthenogenetic algorithm (PGA) is suggested to address the optimization problem. The proposed model and optimization algorithms are tested based on a deep-sea OWF with 56 wind turbines (WTs). The simulation results show that considering wind power curtailment during the DC series-parallel system planning helps to save the levelized cable cost of energy (LCCOE) in the long term, and putting the wiring direction of the series as perpendicular as possible to the prevailing wind direction of the OWF helps to increase the power generation of the OWF and reduce LCCOE.